2009
DOI: 10.2308/accr.2009.84.3.839
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Internal Control over Financial Reporting: A Comparison of Regulatory Regimes

Abstract: This study examines the association between corporate governance and disclosures of material weaknesses (MW) in internal control over financial reporting. We study this association using MW reported under Sarbanes-Oxley Sections 302 and 404, deriving data on audit committee financial expertise from automated parsing of member qualifications from their biographies. We find that a lower likelihood of disclosing Section 404 MW is associated with relatively more audit committee members having accounting and superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
318
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(365 citation statements)
references
References 29 publications
15
318
0
4
Order By: Relevance
“…Two o f these limitations are the use o f cross sectional data from annual reports o f a small community which limits the generalisability of our findings, and the assumption made in the empirical part of paper that the members o f the board of directors uniformly affect the decisions to disclose performance information in the annual report. Regarding the latter, the expertise o f non-executive board members may influence a firm 's corporate disclosure practices (Hoitash et al, 2009). In addition, powerful actors on the board may form dominant coalitions which control the decision-making processes at strategic level (Zajac and W estphal, 1996;Carpenter and W estphal, 2001;Golden and Zajac, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Two o f these limitations are the use o f cross sectional data from annual reports o f a small community which limits the generalisability of our findings, and the assumption made in the empirical part of paper that the members o f the board of directors uniformly affect the decisions to disclose performance information in the annual report. Regarding the latter, the expertise o f non-executive board members may influence a firm 's corporate disclosure practices (Hoitash et al, 2009). In addition, powerful actors on the board may form dominant coalitions which control the decision-making processes at strategic level (Zajac and W estphal, 1996;Carpenter and W estphal, 2001;Golden and Zajac, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the findings of Hoitash et al (2009) showed that the better internal controls complying with the COSO standards led to the better implementation of the corporate governance principles. The result once again showed the importance of the link between organizational structure and risk management.…”
Section: Barjaktarević L Pindžo R đUlić K Vjetrov Amentioning
confidence: 99%
“…The audit committee member must also have the ability and knowledge of how to analyze a financial report. Zhang et al (2007), Hoitash et al (2009), andSharma et al (2009) state that the audit committee with only a few accounting and financial expertise with no finance and accounting background is related with a weaker internal control of the company.…”
Section: Audit Committeementioning
confidence: 99%